Between excellence and equity : the case of the germaneducation system - Kotthoff, Hans-Georg (Revista Española de Educación Comparada, 2011)
The paper provides a selective analysis of the strengths and weaknesses of the current German education system. After an introduction to the historical development, the administration and structure of the German education system, the author focuses on three ‘fields oftension’in particular,which will need to be successfully managed by any ‘excellent’ education system: the tension between selectivity and comprehensiveness of the school level, the balance of equity and excellence and the tension between academic subject knowledge and didactic skills in teacher education. The analyses are mainly based on the empirical evidence provided by the various PISA studies, which have had a major impact on educational reformsin Germany since 2000.In conclusion, the author points out, that while the implemented educational reforms have improved some of the deficits identified in the PISA studies,the equity-inequity problem is still very prominent and requires intensified attention. In addition, there is the need for further empirical studies, in order to evaluate the effectiveness of the introduced educational reforms and to facilitate progress towards‘excellence’. El presente artículo ofrece un análisis selectivo de las fortalezas y debilidades del actual sistema educativo alemán. Tras una introducción sobre su desarrollo histórico, su administración y su estructura, el autor se detiene particularmente en tres «campos de tensión» del sistema educativo alemán que necesitan gestionarse de manera exitosa por un sistema educativo «excelente»: la tensión entre la selección y la comprensividad de los niveles educativos, el equilibrio entre la equidad y la excelencia y la tensión entre el conocimiento académico de las asignaturas y las competencias docentes en la formación del profesorado. El análisis se fundamenta principalmente en la evidencia empírica ofrecida por los diversos estudios PISA que han tenido un amplio impacto en las reformas educativas alemanas desde el año 2000. Como conclusión el autor enfatiza que, mientras las reformas educativas implementadas han mejorado algunas de las deficiencias identificadas en los estudios de PISA, la cuestión equidad-inequidad todavía tiene una presencia acusada y requiere una atención más intensa, además, se pone de manifiesto la necesidad de estudios empíricos posteriores que permitan evaluar la efectividad de las reformas educativas emprendidas y se facilite así el verdadero progreso hacia la excelencia.